2006
DOI: 10.1016/j.ijgo.2006.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse — A persistent preventable risk for congenital anomalies

Abstract: ALC in pregnancy continued to be an important factor independently associated with an increased incidence of a broader range of congenital anomalies than previously recognized. Risk for anatomic anomalies was increased in offspring of ALC women over age 30, consistent with previous reports of increased risk of neurobehavioral abnormality in offspring of women over 30.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Existe un hecho que se ha estudiado y comunicado y es la relación que existe entre hábitos de vida de las madres, como consumo de alcohol, drogas y tabaco y la aparición de MFC en sus hijos [11][12][13][14][15] .…”
Section: Discussionunclassified
“…Existe un hecho que se ha estudiado y comunicado y es la relación que existe entre hábitos de vida de las madres, como consumo de alcohol, drogas y tabaco y la aparición de MFC en sus hijos [11][12][13][14][15] .…”
Section: Discussionunclassified
“…Epidemiological studies have reported a significant increase in the number of congenital abnormalities of the respiratory tract in children born to women who had abused alcohol during pregnancy (4). Studies in rodents have also shown that exposure to high levels of ethanol in midgestation (41) or throughout pregnancy (23) decreases fetal lung growth.…”
mentioning
confidence: 99%
“…Existen numerosas publicaciones que demuestran la importancia que tienen como factores de riesgo para MFC, el consumo de alcohol, tabaco y drogas (24)(25)(26)(27).…”
Section: Discussionunclassified